A mouse model of immunosuppression facilitates oral Candida albicans biofilms, bacterial dysbiosis and dissemination of infection - Raja Veerapandian; Anuja Paudyal; Sarah M. Schneider; Sonny T. M. Lee; Govindsamy Vediyappan; Govindsamy Vediyappan (Frontiers in Cellular and Infection Microbiology)
Opportunistic pathogens are a major threat to people, especially those with impaired immune systems. Two of the most important microbes in this category are the fungus Candida albicans and Gram-positive bacteria of the genus Enterococcus, which share overlapping niches in the oral cavity, gastrointestinal and urogenital tracts. The clinical importance of oral C. albicans biofilm and its interaction with the host under immunosuppressive conditions remains largely understudied. Here, we used a mouse model of oropharyngeal candidiasis (OPC) with cortisone acetate injection on alternate days and a continuous supply of C. albicans in drinking water for three days, resulting in immunosuppression. Results showed abundant growth of resident oral bacteria and a strong C. albicans biofilm on the tongue consisting of hyphae which damaged papillae, the epidermal layer, and invaded tongue tissue with the accumulation of inflammatory cells as demonstrated by Grocott’s methenamine silver and hematoxylin and eosin staining, respectively. The dispersed microbes from the oral biofilm colonized the gastrointestinal (GI) tract and damaged its integrity, disseminating microbes to other organs. Although no visible damage was observed in the kidney and liver, except increased lipid vacuoles in the liver cells, C. albicans was found in the liver homogenate. Intriguingly, we found co-occurrence of Enterococcus faecalis in the tongue, liver, and stool of immunosuppressed control and C. albicans infected organs. Targeted 16S rRNA and ITS2 amplicon sequencing of microbes from the fecal samples of mice confirmed the above results in the stool samples and revealed an inverse correlation of beneficial microbes in the dysbiosis condition. Our study shows that mucosal-oral infection of C. albicans under immunosuppressed conditions causes tissue damage and invasion in local and distant organs; the invasion may be aided by the overgrowth of the resident endogenous Enterobacteriaceae and other members, including the opportunistic pathogen Enterococcus faecalis.